Sistemas eletrônicos em duas dimensões : desordem e resposta dinâmica - Silva, Cláudio José da (Universidade Federal de São Carlos, 2009)
In disordered systems the pinning strength on the carriers due to impurities or defects is one of the most important mechanisms that produce insulator behavior. A transition to a metal phase should occur if a driving field is applied to the system. In the last three decades, such transition in two-dimensional systems has attracted much attention in light of the fascinating experimental observations. However, the physics behind these observations is at the moment not entirely understood. Experiments relating nonlinear behavior of the conductivity and the dynamical response in such systems in the presence of disorder have motivated several theoretical proposals and numerical calculations in order to establish a better understanding of these phenomena. In this work we have studied, by means of Langevin molecular dynamics simulation, a classical two-dimensional system of electrons on liquid helium films adsorbed on a solid substrate subject to an external electric field parallel to the surface of the helium, which produces a driving force. This system is an ideal prototype for the two-dimensional electron gas formed on semiconductor heterostructures. Also, electrons floating on a liquid helium surface have been one of the most promising candidates as a base for quantum computing. To simulate a pinning center we constrain our system by imposing an in-plane potential with lorentzian shape. Firstly, we analyze the influence of the film thickness and the kind of substrate on the drift electron velocity as a function of the external driven force, which is directly related with the dc conductivity. Secondly, the dependence with temperature and disorder strength of the depinning was considered in the extent of the scaling behavior. Our results are in excellent agreement with several experiments and should elucidate better the dynamical response phenomena in 2D electronic systems in the presence of pinning disorder.
Keywords: Elétrons em filme de hélio; Dinâmica molecular; Desordem; Sistema de dimensionalidade reduzida; Condutividade elétrica; CIENCIAS EXATAS E DA TERRA::FISICA